The emergence and dissemination of whitefly-transmitted geminiviruses in Latin America - Morales, Francisco José; Anderson, Pamela K. (Springer, 2001)
The proliferation and rapid dissemination of whitefly-transmitted viruses of important food and industrial crops in Latin America, have been the consequence of drastic changes in traditional cropping systems. Some of the expanding non-traditional cash and export crops, such as soybean and several vegetables, have served as suitable reproductive hosts for the whitefly Bemisia tabaci. This insect pest has been shown to transmit at least 20 different geminiviruses that affect different commercial and basic food crops in Latin America. This review summarizes the existing knowledge on this important group of viruses and their vector in this region.